Tart of darkness - Swanson, Denise (Swanson, Denise. Chef-to-go mystery, 2018)
After unexpectedly inheriting a huge old house in a small college town, Dani, to fund her new personal chef business, takes in boarders, but when one of them is murdered and she becomes the prime suspect, she must serve up the real killer to clear her name and save her business.